Start-upy telemedyczne w Polsce — trendy i kierunki rozwoju - Cuda, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The Polish medical market reports agrowing demand for innovative solutions in the field of health protection — the use of information and communication technologies in the provision of medical services contributes to an increase in their efficiency and effectiveness. Telemedicine is data transfer and the provision of medical services to patients remotely, using new technology solutions. The main purpose of this paper is to analyze the current situation of the telemedicine market in Poland, especially new technology startups devoted to telemedicine solutions, and to identify investment trends. Technology development should be aprocess of targeted changes aimed at improving a certain process, bearing in mind the auxiliary and, above all, the increasingly crucial nature of new technologies in the process of patient treatment by specialists in the field of medicine. This study has been conducted in order to ascertain the attitudes of investors with capital of more than 50,000 euro, to the changing technological environment, which is intended to improve the provision of medical services and contribute to an increase in the quality of healthcare, and their willingness to invest in startups in the telemedicine industry.
Keywords: telemedicine; healthcare market